2016
DOI: 10.1080/14767058.2016.1179274
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sublingual misoprostol for induction of labor at term and post term according to parity and membrane integrity: a prospective observational study

Abstract: Sublingually administered misoprostol is an effective and safe method for induction of Labor at term. Parity, status of membranes and BMI significantly affect time to delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…This allowed us to observe better foetal outcomes than those of the Expedite study while maintaining a non-negligible percentage of NICU admission of 2% and 4 cases of neonatal pH < 7.0 (1%). However, the percentages of admission to NICU as well as the percentages of Caesarean sections were not significantly different from those observed in a large cohort of IOL with 25 mg of sublingual misoprostol (21).…”
Section: Discussioncontrasting
confidence: 73%
“…This allowed us to observe better foetal outcomes than those of the Expedite study while maintaining a non-negligible percentage of NICU admission of 2% and 4 cases of neonatal pH < 7.0 (1%). However, the percentages of admission to NICU as well as the percentages of Caesarean sections were not significantly different from those observed in a large cohort of IOL with 25 mg of sublingual misoprostol (21).…”
Section: Discussioncontrasting
confidence: 73%
“…Brusati et al 22 evaluated the efficacy of 25 µg of sublingual misoprostol in inducing labor in single births. They found that vaginal birth occurred within 24 hours in 78% of multiparous women and in 65% of nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Our secondary analysis showed that patients induced for PROM had a better response to the protocol, and even more so if their term at PROM was advanced. Only a few trials have reported data with PROM for IOL with oral misoprostol: “Membrane status brought an additional significant impact on time-to-vaginal delivery as main outcome measure of efficacy” [ 23 ]. Our cohort only included 75 patients with PROM, and thus the power was insufficient to draw certain conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…We know that parity affects time to delivery: “The percentage of vaginal delivery within 24 h is higher in multiparous women than in nulliparous” [ 23 ]. As in the literature, with our multivariable analysis, nulliparity seemed to be a factor indicating poor response to the protocol.…”
Section: Discussionmentioning
confidence: 99%